ANTAGONISTIC YEASTS AND ALTERNATIVE CHEMICAL COMBINATIONS AS POTENTIAL BIOCONTROL AGENTS IN POSTHARVEST APPLICATION - Mahunu, G. K; Abubarkari, A-H; Garti, H. (UDS International Journal of Development, 2020)
Synthetic chemical residues inflict unrepairable damage on living things and the ecology, hence the need to search for safer and more effective alternative methods for postharvest disease management. To make these alternative methods economically viable, their resilient and persistent performance must be improved. Several studies suggest that combining two or more alternative biocontrol agents give them broad-spectrum potency against postharvest diseases. In line with this, remarkable progress has been made toward development of multifaceted approaches at each stage of the disease control process. The present review highlights these alternative integrated biocontrol measures, their consequential effects on stored fruit and corresponding mechanisms of action in postharvest disease control. It also reviewed the challenges involved in the application of postharvest biocontrol agents. Key words: Postharvest, Penicillium expansum, Biological Agents, Unconventional Chemicals Compounds, Antagonistic Yeasts